Advances in Automation : Proceedings of the International Russian Automation Conference, RusAutoCon 2019, September 8-14, 2019, Sochi, Russia /: Proceedings of the International Russian Automation Conference, RusAutoCon 2019, September 8-14, 2019, Sochi, Russia. (2020) - Unknown
No abstract available